Augusto Matraga: um hérói além do bem e do mal - uma perpectiva trágico-ntológica - Leitão, Eduardo José Pereira de Sá (2006)
The present dissertation analyses the philosophy of Friedrich Nietzsche (1844-1900) and the short story written by João Guimarães Rosa (1908-1967), A hora e vez de Augusto Matraga (1946) seeking to point out the possibility of the philosophic application of some Nietzschean ideas to enlarge the aesthetic value of the short story. It has been especially aimed at applying the concept of the noble superior being described by Nietzsche, the ubermensch, to the hero s ontological nature, Augusto Matraga. Nietzsche s postulates of the will to power, the elements suggested of the trial between Dionysus and Apollo and the ascetic ideal, will be especially relevant to this work, which intends to establish until what point the hero can be conceived as a good ascetic person, in so far as his noble ontological nature trespass the Christian morality, bringing him closer to the man who, according to Nietzsche, is beyond good and evil. Some Heideggerian concepts will also be relevant in order to reinforce the idea that the judgment created about Matraga is just an appearance that does not contemplate his essential Being, contributing to veil his real tragic-ontological valour, what implies that the aesthetic power of the short has been under valued